Analysis of food products using optical methods - Yeremenko, Yelyzaveta; Litvynchuk (Vorontsova), Svitlana (My University, 2025)
The analysis of food products by applying optical methods allows for monitoring without the need for intervention in the technological process, which helps to reduce the risk of contamination or damage to products and guarantee the high quality of the final product.
Keywords: optical methods; food quality; оптичні методи; якість харчових продуктів; кафедра фізики та професійної безпеки